Water and Wastewater Treatment in India: A Qualitative Analysis of An Emerging Market - Balasubramani, Radhika (2006)
Rising demands from agriculture, industry and a growing population has left India thirsty for one of the basic necessities of life water. Unplanned industrialisation, urbanisation, and the impact of liberalised import of wastes intended for recycling have negatively affected the water environment in India, and is now one of the major concerns of the economy. However, major reformation is taking place in the industrial water sector coercing enterprises to invest in pollution abatement technology. Stricter enforcement of environmental regulations leaves no choice for polluting industries but to comply, rather than face the penalty of non compliance.